2022
DOI: 10.3390/jof8121239
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Institutional Database Review of Orbital Complications and Survival Outcomes in Adult Patients with Invasive or Non-Invasive Fungal Rhinosinusitis

Abstract: Background: Invasive fungal rhinosinusitis (IFS) with orbital complications has remained a challenging disease over the past few decades. Only a few studies have been conducted to investigate the factors associated with orbital complications in fungal rhinosinusitis (FRS). We aimed to review the characteristics between IFS and non-invasive fungal rhinosinusitis (NIFS) and determine clinical factors associated with orbital complications and overall survival. Methods: A multi-institutional database review study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In this study, patients with isolated sphenoid rhinosinusitis and diabetes mellitus or malignant neoplasms were prone to orbital complications. A previous study reported that high blood glucose and C-reactive protein levels were risk factors for orbital complications in patients with non-invasive fungal rhinosinusitis [30]. Those laboratory data suggested an immunosuppressive status and systemic inflammation [30].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In this study, patients with isolated sphenoid rhinosinusitis and diabetes mellitus or malignant neoplasms were prone to orbital complications. A previous study reported that high blood glucose and C-reactive protein levels were risk factors for orbital complications in patients with non-invasive fungal rhinosinusitis [30]. Those laboratory data suggested an immunosuppressive status and systemic inflammation [30].…”
Section: Discussionmentioning
confidence: 93%
“…A previous study reported that high blood glucose and C-reactive protein levels were risk factors for orbital complications in patients with non-invasive fungal rhinosinusitis [30]. Those laboratory data suggested an immunosuppressive status and systemic inflammation [30]. Patients with diabetes mellitus or malignant neoplasms are usually considered relatively immunocompromised and could be susceptible to complications of rhinosinusitis [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Invasive fungal sinusitis is rare, which accounts for 3.6% of all fugal sinusitis. 4 ) The middle turbinate is the commonly affected site, and the various presenting symptoms include fever, headache, rhinorrhea, facial pain, and diplopia. 5 ) Invasive fungal sinusitis is associated with rapid infiltration and destruction of adjacent tissues, such as the facial bone, and is therefore occasionally misdiagnosed as a tumor.…”
Section: Discussionmentioning
confidence: 99%